Cupido from Dusk Till Dawn: A Collection of the Best Erotic Short Stories - Cupido (Saga Egmont, 2023)
'Cupido from Dusk Till Dawn: A Collection of the Best Erotic Short Stories' is an anthology of great, sexual fiction that will pleasure you from dusk till dawn; with tales of summer romances, threesomes, and even frisky public encounters, there's something to suit everyone's fantasy.This is an erotic short story collection from Cupido. The collection includes the following compilations: 'Three Happy People', 'The Hitchhikers', 'You, Me and my Friend', 'The Architect, Me and the Bartender', 'Two and Two are Four', 'The Mask', 'As Usual', 'Horny and Longing', 'The Surprise', 'Elisabeth's Day', 'Blind Man's Bluff', 'Hole in one', 'The Mystical Smile', 'Carpe Diem', 'The Mountain Hike', 'Summer in the Kayak', 'Blind Passion', 'The Friend in the Shower', 'Her Lover', 'Conquest', 'A Wet Walk in the Forest', 'Bus Trip', 'The Dryad', 'Strange Waves', 'A Day by the Sea', 'Singles holiday', 'Make love', 'A Journey for Two', 'An 'Innocent' Trip to the Beach', 'Tropical Heat', 'The Temptations of Summer', 'The Trial Voyage', 'Beach Joys', 'An Autumn Walk in the Woods', 'New Year's Party at Naomi's', 'Queen of the Kitchen', 'A Naughty Dinner', 'Summer Fling' and 'The Dream About Lena'.